Midface fractures: a studying 6.5 years results - MH. Ansari (Tehran University of Medical Sciences, 1995)
Midface is located between frontal bone and occlusal surface of maxillary teeth. For edentulous patients, alveolar process of maxilla is considered. Midface fractures are known as maxillary fractures which are not an appropriate term to use instead of midface fractures.